2019
DOI: 10.1186/s12974-018-1389-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term characterization of activated microglia/macrophages facilitating the development of experimental brain metastasis through intravital microscopic imaging

Abstract: BackgroundMicroglia/macrophages (M/Ms) with multiple functions derived from distinct activation states are key surveillants maintaining brain homeostasis. However, their activation status and role during the brain metastasis of malignant tumors have been poorly characterized.MethodsHeterozygous CX3CR1-GFP transgenic mice were used to visualize the dynamic changes of M/Ms during the development of experimental brain metastasis through long-term intravital imaging equipped with redesigned bilateral cranial windo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 69 publications
1
49
0
Order By: Relevance
“…However, Chuang et al demonstrated that tumor cells block pro-apoptotic functions of microglia and exploit tissue damage responses to increase their invasive capacity (86). The role of microglia in tumor cell extravasation was further confirmed by Qiao et al using a CSF1R inhibitor to deplete microglia in prevention trial settings in a mouse model for melanoma BrM (84). The authors also found that Mmp3 expression by microglia was negatively correlated with ZO-1 expression on endothelial cells.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…However, Chuang et al demonstrated that tumor cells block pro-apoptotic functions of microglia and exploit tissue damage responses to increase their invasive capacity (86). The role of microglia in tumor cell extravasation was further confirmed by Qiao et al using a CSF1R inhibitor to deplete microglia in prevention trial settings in a mouse model for melanoma BrM (84). The authors also found that Mmp3 expression by microglia was negatively correlated with ZO-1 expression on endothelial cells.…”
Section: Introductionmentioning
confidence: 85%
“…Although the BrM field currently lacks detailed insight into the molecular identity of disease-associated macrophages/microglia compared to neurodegenerative diseases or primary brain tumors, a series of pre-clinical studies shed light into tumor-associated macrophage (TAM) functions during distinct steps of the metastatic cascade. Invasion of metastasizing tumor cells is rapidly sensed by microglia and the presence of single tumor cells is sufficient to recruit and to activate microglia (84, 85). Given the role of microglia in immune surveillance and host defense, it is tempting to speculate that the initial contact between tumor cells and microglia at sites of extravasation leads to clearance of invading tumor cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depletion of microglia and macrophages by treatment with PLX3397, an inhibitor of colony stimulating factor-1 receptor (CSF-1R), reduced the total number and mean size of the brain metastases by 83 and 65%, respectively. Microglia and macrophages from metastatic brains expressed MMP3 and treatment with PD166793, an MMP inhibitor, reduced the total number and mean size of the brain metastases by 50 and 53%, respectively (82). In a transplantable model of B16 melanoma cells the presence of microglia (CD11b+F4/80+CD45 low ) infiltration into intracranial B16 melanoma tumors increased following combined PD-1/CTLA-4 blockade and the increase in microglia correlated with intracranial therapeutic efficacy.…”
Section: Immune Microenvironment Of Melanoma Metastasesmentioning
confidence: 99%